THE IMPACT OF FACEBOOK SOCIAL NETWORKING SITES ON YOUTH PSYCHOLOGY DEVELOPMENT - Nengsih Nengsih (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2018)
The increasing use of Facebook social networking sites, most of which are teenagers, is a growing phenomenon at this time. As a result the positive and negative impacts that social media poses have an impact on their use. Facebook's social networking site influences the development of adolescent psychology, both physically (brain / amygdala), cognitive, social, personality, moral and religious. The purpose of this paper is to look at the impact of Facebook social networking sites on the development of adolescent psychology. Based on the results of the discussion that the impact of Facebook's social networking site on the development of adolescent psychology, among others: 1) Facebook as a medium for expressing feelings and channeling emotions, 2) Conflict of teenagers in using Facebook, 3) Facebook media for searching for identity and means of socialization, 4) Influencing time management of adolescents.